(3QSGdI GdSjQI GdeSJbjeIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3Jhcdf Ydi ehdGfG GdHGQ GdYdGe HSe Gddg GdQMef GdQMje UaGJ YHOg GdEeGe QShe GdfWbGA GdMThjI hePGgH GdXhGgQ GdfGehSjI s
(3BNQgG (B:s
(3hEPG YHOJehg adCfaSce egOJe hEf caQJe HdGghJg aYdjce GdNRi hGdYPGH hGdMeO hGdTcQ dehdGfG hMOg ai GdSQGA hGdVQGA hGdTOI hGdQNGA JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds